ISLAMIC ECONOMIC PUBLICATIONS IN THE DEVELOPMENT OF FINANCIAL SYSTEM STABILITY RESEARCH: A BIBLIOMETRIC ANALYSIS - Firmansyah, Irman (Al-Infaq: Jurnal Ekonomi Islam, 2023)
This study aims to determine the role of Islamic economic publications in developing research on financial system stability through mapping research results. This research was conducted on journal articles indexed by dimensions.ai from 2017 to 2021. The analysis was carried out by bibliometrics using the R Biblioshiny software. The results show that non-Islamic economic journals dominate the development of journals that publish the theme of financial system stability. There is only one journal that is most relevant to the theme of financial system stability in Islamic economics and is in the top 20, namely "Journal of Islamic Monetary Economics and Finance". Likewise, only one journal that has a major impact on Islamic economics is the "International Journal of Islamic and Middle Eastern Finance and Management". The most relevant writers on the theme of financial system stability are Li J, Wang Y, Zhang J, and Zhang Z. However, the most productive is Li J and the one with the biggest impact is Chen Y. Then the country with the most citations is Hong Kong followed by the USA and India. Research with this theme is predicted to increase again in the years to come and is related to the impact of the COVID-19 pandemic. Meanwhile, the system has not detected the relationship with the Islamic economy.